Factors Affecting The Market Value of a Sample of Banks Listed in The Iraqi Stock Exchange (NTU journal for Administrative and Human Sciences (JAHS), 2023)
The market value of the stock is one of the basic criteria and indicators that are used to express the value of economic units, whether companies or banks. The market share price is often used synonymously with the market value, and there are a number of variables that affect the market value, they are represented in financial intelligence, volumetric efficiency, fixed volume return and variable volume return. So the research seeks to show the extent of the impact of these variables on the market value. The research problem stems from Iraq’s quest to join the World Trade Organization; the research assumes that there is a positive, statistically significant relationship between the variables of financial intelligence, volumetric efficiency, fixed volume return and variable volume return with the market value of Iraqi bank shares; the aim of the research was to study the impact of financial intelligence, volumetric efficiency, fixed volume return and variable volume return on the market value of Iraqi bank shares, the subject of the sample. The research came in two sections, the first of which dealt with the factors affecting the market value of shares, while the second dealt with statistical treatment methods, the research reached a number of important results, perhaps the most important of which is what confirms the nature of the positive relationship between market value and financial intelligence, the research recommended the need to reconsider the relationship between market value and volumetric efficiency, because volumetric efficiency, which measures the volume of service activities provided by the bank, and it is inversely proportional to the optimum size and its actual productivity.